Preliminary checklist of ferns and lycophytes in the upper montane Forest of Mt. Balatukan, Gingoog City, Southern Philippines - Pescuela, Gretl Rae P. (Philippine Journal of Science, 2024)
A preliminary species checklist of ferns and lycophytes in the upper montane forest of Mt. Balatukan, Gingoog City, Southern Philippines was provided, including their conservation and ecological status assessments. Specimens were collected through repeated transect walks. Species inventory revealed a total of 112 species (16 were lycophytes and 97 were ferns) belonging to 61 genera and 23 families. The top five families with the highest species richness are Polypodiaceae, Lycopodiaceae, Dryopteridaceae, Hymenophyllaceae, and Lindsaeaceae. In addition, most of the collected specimens were terrestrial and epiphytic. In terms of its conservation status and ecological status, out of 16 threatened species, seven are endangered (Phlegmariurus salvinoides, P. squarossus, Dicksonia mollis, Lepisorus platyrhynchos, Ophioglossum ramosii, O. pendulum, and Tmesipteris zamorarum), five are vulnerable (Alsophila fuliginousa, Asplenium vittaeforme, Aglaomorpha cornucopia, Botrychium daucifolium, and Sphaeropteris elmeri), three are other wildlife species (Lindsaea apoensis, Polystichum elmeri, and Callisopteris apiifolia), and only one other threatened species (Angiopteris evecta). Lastly, nine species of pteridophytes are widely distributed in the Philippines, and one species is narrowly distributed in Mindanao, with the family Lindsaeaceae and Polypodiaceae having the highest number of endemic species.